Beyond Neoliberalism in Latin America?
X, 277 p. 4 illus.
Keywords: While the neoliberal model continues to dominate economic and political life in Latin America, people throughout the region have begun to strategize about how to move beyond this model. Twelve cutting-edge papers investigate how Latin Americans are struggling to articulate a future in which neoliberalism is reconfigured.